Inhibition of NF-κB pathways alleviates hydrocephalus via modulation of choroid plexus epithelium inflammation in a rat intraventricular hemorrhage model - Tong Sun; Yikai Yuan; Yicheng Zhou; Ke Wu; Chao You; Junwen Guan (PLoS ONE, 2025)
Backgrounds Post-hemorrhagic hydrocephalus (PHH) is a serious complication following hemorrhagic events due to cerebrospinal fluid (CSF) pathway disorders. We explore the Nuclear Factor κB (NF-κB) signaling pathway’s involvement in choroid plexus epitheliums (CPEs) inflammation and hydrocephalus, aiming to identify new therapeutic targets for managing PHH. Materials and Methods Adult male Sprague-Dawley rats were used to establish an intraventricular hemorrhage (IVH) autologous-blood model. Rats were randomly assigned to four groups: artificial cerebrospinal fluid (aCSF), IVH, IVH + TNF-α inhibitor, and IVH + NF-κB inhibitor. CSF secretion rates, lateral ventricular volumes, and inflammatory cytokine levels in CSF were measured at 3, 7, and 14 days post-modeling. Western blotting and immunofluorescence were used to analyze NF-κB pathway activation and the related inflammatory markers, including NF-κB, TNF-α, Illinois, Na+-K+-Cl− co-transporter 1 (NKCC1), aquaporin-1 (AQP1), and aquaporin-4 (AQP4), Results TNF-α and NF-κB inhibitors effectively reduce lateral ventricular enlargement and CSF secretion rates following IVH in rats. The concentration of TNF-α in the IVH group was significantly higher than in the aCSF group as well as the two inhibitor groups. On days 3 and 7 post-modeling, Western blot and immunofluorescence analyses revealed altered expression of pNF-κB (p65), and proteins in CPEs across groups, with TNF-α and NF-κB inhibition reducing pNF-κB and levels. Illinois and NKCC1 changes were tissue, Conclusions NF-κB activation post-IVH drives CPEs inflammation, increases CSF production, and contributes to hydrocephalus formation. Targeting the NF-κB pathway offers a promising strategy for the treatment of PHH.